Dose of physical activity, physical functioning and disability risk in mobility-limited older adults: Results from the LIFE study randomized trial. - Fielding, Roger A; Guralnik, Jack M; King, Abby C; Pahor, Marco; McDermott, Mary M; Tudor-Locke, Catrine; Manini, Todd M; Glynn, Nancy W; Marsh, Anthony P; Axtell, Robert S; Hsu, Fang-Chi; Rejeski, W Jack; et al. (PLoS ONE, 2017)
Understanding the minimal dose of physical activity required to achieve improvement in physical functioning and reductions in disability risk is necessary to inform public health recommendations. To examine the effect of physical activity dose on changes in physical functioning and the onset of major mobility disability in The Lifestyle Interventions and Independence for Elders (LIFE) Study. We conducted a multicenter single masked randomized controlled trial that enrolled participants in 2010 and 2011 and followed them for an average of 2.6 years. 1,635 sedentary men and women aged 70-89 years who had functional limitations were randomized to a structured moderate intensity walking, resistance, and flexibility physical activity program or a health education program. Physical activity dose was assessed by 7-day accelerometry and self-report at baseline and 24 months. Outcomes included the 400 m walk gait speed, the Short Physical Performance Battery (SPPB), assessed at baseline, 6, 12, and 24 months, and onset of major mobility disability (objectively defined by loss of ability to walk 400 m in 15 min). When the physical activity arm or the entire sample were stratified by change in physical activity from baseline to 24 months, there was a dose-dependent increase in the change in gait speed and SPPB from baseline at 6, 12, and 24 months. In addition, the magnitude of change in physical activity over 24 months was related to the reduction in the onset of major mobility disability (overall P < 0.001) (highest versus the lowest quartile of physical activity change HR 0.23 ((95% CI:0.10-0.52) P = 0.001) in the physical activity arm. We observed a dose-dependent effect of objectively monitored physical activity on physical functioning and onset of major mobility disability. Relatively small increases (> 48 minutes per week) in regular physical activity participation had significant and clinically meaningful effects on these outcomes., TRIAL REGISTRATION: ClinicalsTrials.gov NCT00116194.
89 citations (Crossref) [2023-10-31] Place: United States Fielding, Roger A. Nutrition, Exercise Physiology, and Sarcopenia Laboratory, Jean Mayer USDA Human Nutrition Research Center on Aging at Tufts University, Boston, MA, United States of America. Guralnik, Jack M. Department of Epidemiology and Public Health, University of Maryland School of Medicine, 4655 W. Baltimore Street, Baltimore, MD, United States of America. King, Abby C. Department of Health Research & Policy, and Stanford Prevention Research Center, Department of Medicine, Stanford University Medical School, Stanford, CA, United States of America. Pahor, Marco. Department of Aging and Geriatric Research, University of Florida College of Medicine, Gainesville, FL, United States of America. McDermott, Mary M. Department of Medicine, Northwestern University Feinberg School of Medicine, 750 N Lake Shore Drive, 10th Floor, Chicago, IL, United States of America. Tudor-Locke, Catrine. Department of Kinesiology, University of Massachusetts Amherst, Amherst, MA, United States of America. Tudor-Locke, Catrine. Pennington Biomedical Research Center, Louisiana State University System, Baton Rouge, LA, United States of America. Manini, Todd M. Department of Aging and Geriatric Research, University of Florida College of Medicine, Gainesville, FL, United States of America. Glynn, Nancy W. Center for Aging and Population Health, Department of Epidemiology, Graduate School of Public Health, University of Pittsburgh, Pittsburgh, PA, United States of America. Marsh, Anthony P. Department of Health and Exercise Science, Wake Forest University, Winston-Salem, NC, United States of America. Axtell, Robert S. Department of Exercise Science, Southern Connecticut State University, New Haven, CT. Hsu, Fang-Chi. Department of Biostatistical Sciences, Division of Public Health Sciences, Wake Forest School of Medicine, Winston-Salem, NC, United States of America. Rejeski, W Jack. Center for Aging and Population Health, Department of Epidemiology, Graduate School of Public Health, University of Pittsburgh, Pittsburgh, PA, United States of America.
Keywords: *Activities of Daily Living; *Disabled Persons; *Exercise; *Mobility Limitation; Activities of Daily Living; Aged; Aged; 80 and over; Article; Disabled Persons; Exercise; Female; Humans; Male; Mobility Limitation; accelerometry; aged; controlled study; daily life activity; dept.hms; disabled person; education program; exercise; exercise intensity; female; human; incidence; major clinical study; male; multicenter study; outcome assessment; peer-reviewed; physical activity; physical activity; capacity and performance; physical disability; physical functioning; physical mobility; physical performance; randomized controlled trial; resistance training; risk assessment; risk factor; sedentary lifestyle; self report; very elderly; walking difficulty; walking speed

Actigraphy features for predicting mobility disability in older adults - Kheirkhahan, Matin; Tudor-Locke, Catrine; Axtell, Robert; Buman, Matthew P.; Fielding, Roger A.; Glynn, Nancy W.; Guralnik, Jack M.; King, Abby C.; White, Daniel K.; Miller, Michael E.; Siddique, Juned; Brubaker, Peter; et al. (Physiological Measurement, 2016)
Actigraphy has attracted much attention for assessing physical activity in the past decade. Many algorithms have been developed to automate the analysis process, but none has targeted a general model to discover related features for detecting or predicting mobility function, or more specifically, mobility impairment and major mobility disability (MMD). Men (N = 357) and women (N = 778) aged 70-89 years wore a tri-axial accelerometer (Actigraph GT3X) on the right hip during free-living conditions for 8.4 +/- 3.0 d. One-second epoch data were summarized into 67 features. Several machine learning techniques were used to select features from the free-living condition to predict mobility impairment, defined as 400 m walking speed ¡0.80 m s(-1). Selected features were also included in a model to predict the first occurrence of MMD-defined as the loss in the ability to walk 400 m. Each method yielded a similar estimate of 400 m walking speed with a root mean square error of similar to 0.07 m s(-1) and an R-squared values ranging from 0.37-0.41. Sensitivity and specificity of identifying slow walkers was approximately 70% and 80% for all methods, respectively. The top five features, which were related to movement pace and amount (activity counts and steps), length in activity engagement (bout length), accumulation patterns of activity, and movement variability significantly improved the prediction of MMD beyond that found with common covariates (age, diseases, anthropometry, etc). This study identified a subset of actigraphy features collected in free-living conditions that are moderately accurate in identifying persons with clinically-assessed mobility impaired and significantly improve the prediction of MMD. These findings suggest that the combination of features as opposed to a specific feature is important to consider when choosing features and/or combinations of features for prediction of mobility phenotypes in older adults.
Citation Key Alias: lens.org/144-715-377-748-547 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometers; Actigraphy; Analysis process; Artificial intelligence; Data mining; Disability; Feature extraction; Forecasting; Free livings; General model; Learning systems; Living conditions; Mean square error; Older adults; Patient monitoring; Physical activity; Sedentary; Walking aids; Walking speed; aging; data mining; dept.hms; disability; machine learning; physical activity; sedentary; ⚠️ Invalid DOI

Evaluating accelerometry thresholds for detecting changes in levels of moderate physical activity and resulting major mobility disability - Rejeski, W. Jack; Walkup, Michael P.; Fielding, Roger A.; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; McDermott, Mary McGrae; Miller, Emily Y; Newman, Anne B.; Tudor-Locke, Catrine; Axtell, Robert S.; Miller, Michael E. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2018)
Background: An important decision with accelerometry is the threshold in counts per minute (CPM) used to define moderate to vigorous physical activity (MVPA). We explore the ability of different thresholds to track changes in MVPA due to a physical activity (PA) intervention among older adults with compromised function: 760 CPM, 1,041 CPM, and an individualized threshold. We also evaluate the ability of change in accelerometry and self-reported PA to attenuate treatment effects on major mobility disability (MMD). Methods: Data from a week of hip worn accelerometers and self-reported PA data (30-day recall) were examined from baseline, 6-, 12-, and 24-months of follow-up on 1,528 older adults. Participants were randomized to either PA or Health Education (HE). MMD was objectively defined by loss of ability to walk 400 m during the follow-up. Results: The three thresholds yielded similar and higher levels of MVPA for PA than HE (p ¡ .001), however, this difference was significantly attenuated in participants with lower levels of physical function. Self-reported PA that captured both walking and strength training totally attenuated the intervention effect for MMD, an 18% reduction to a 3% increase. Accelerometer CPMs showed less attenuation of the intervention effect. Conclusions: Accelerometry assessment within the LIFE study was not sensitive to change in level in physical activity for older adults with very low levels of physical function. A combination of self-report and objective measures are recommended for use in physical activity intervention studies of the elderly; limitations of accelerometry deserve closer attention.
6 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000430696300014 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometry; Aged; Aged; 80 and over; Female; Geriatric Assessment; Humans; LIFE-study; Male; Mobility Disability; Mobility Limitation; Motor Activity; Older Adults; Thresholds; Walking; accelerometry; aged; clinical trial; controlled study; dept.hms; female; geriatric assessment; human; male; motor activity; multicenter study; peer-reviewed; physiology; procedures; randomized controlled trial; very elderly; walking; walking difficulty

A case for promoting movement medicine: preventing disability in the LIFE randomized controlled trial - Fanning, Jason; Rejeski, W Jack; Chen, Shyhhuei; Nicklas, Barbara J; Walkup, Michael P; Axtell, Robert S; Fielding, Roger A; Glynn, Nancy W; King, Abby C; Manini, Todd M; Mcdermott, Mary Mcgrae; Newman, Anne B; et al. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2019)
Background: The movement profile of older adults with compromised function is unknown, as is the relationship between these profiles and the development of major mobility disability (MMD)-a critical clinical outcome. We first describe the dimensions of movement in older adults with compromised function and then examine whether these dimensions predict the onset of MMD. Methods: Older adults at risk for MMD (N = 1,022, mean age = 78.7 years) were randomized to receive a structured physical activity intervention or health education control. We assessed MMD in 6-month intervals (average follow-up of 2.2 years until incident MMD), with activity assessed at baseline, 6-, 12- and 24-month follow-up via accelerometry. Results: A principal components analysis of 11 accelerometer-derived metrics yielded three components representing lifestyle movement (LM), extended bouts of moderate-to-vigorous physical activity (MVPA), and stationary body posture. LM accounted for the greatest proportion of variance in movement (53%). Within health education, both baseline LM (HR = 0.74; 95% CI 0.62 to 0.88) and moderate-to-vigorous physical activity (HR = 0.69; 95% CI 0.54 to 0.87) were associated with MMD, whereas only LM was associated with MMD within physical activity (HR = 0.74; 95% CI 0.61 to 0.89). There were similar nonlinear relationships present for LM in both physical activity and health education (p ¡ .04), whereby risk for MMD was lower among individuals with higher levels of LM. Conclusions: Both LM and moderate-to-vigorous physical activity should be central in treatment regimens for older adults at risk for MMD.
8 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000491242600017, lens.org/077-007-606-131-474 tex.type: [object Object]
Keywords: Acceleration; Accelerometry; Age Factors; Aged; Aged; 80 and over; Aging; Confidence Intervals; Disability; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Linear Models; Male; Mobility Limitation; Physical Fitness; Physical activity; Prognosis; Sedentary; Sex Factors; Single-Blind Method; Walking Speed; acceleration; age; aged; aging; clinical trial; confidence interval; controlled study; dept.hms; disability; female; fitness; geriatric assessment; human; male; multicenter study; peer-reviewed; physiology; procedures; prognosis; randomized controlled trial; sex factor; single blind procedure; statistical model; very elderly; walking difficulty; walking speed

Promoting physical activity for elders with compromised function: the Lifestyle Interventions and Independence for Elders (LIFE) Study physical activity intervention - Rejeski, W. Jack; Axtell, Robert; Fielding, Roger; Katula, Jeffrey; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; Pahor, Marco; Rego, Alvito; Tudor-Locke, Catrine; Newman, Mark; Walkup, Michael P.; et al. (Clinical Interventions in Aging, 2013)
The Lifestyle Interventions and Independence for Elders (LIFE) Study is a Phase III randomized controlled clinical trial (Clinicaltrials.gov identifier: NCT01072500) that will provide definitive evidence regarding the effect of physical activity (PA) on major mobility disability in older adults (70-89 years old) who have compromised physical function. This paper describes the methods employed in the delivery of the LIFE Study PA intervention, providing insight into how we promoted adherence and monitored the fidelity of treatment. Data are presented on participants' motives and self-perceptions at the onset of the trial along with accelerometry data on patterns of PA during exercise training. Prior to the onset of training, 31.4% of participants noted slight conflict with being able to meet the demands of the program and 6.4% indicated that the degree of conflict would be moderate. Accelerometry data collected during PA training revealed that the average intensity - 1,555 counts/minute for men and 1,237 counts/minute for women - was well below the cutoff point used to classify exercise as being of moderate intensity or higher for adults. Also, a sizable subgroup required one or more rest stops. These data illustrate that it is not feasible to have a single exercise prescription for older adults with compromised function. Moreover, the concept of what constitutes “moderate” exercise or an appropriate volume of work is dictated by the physical capacities of each individual and the level of comfort/stability in actually executing a specific prescription.
36 citations (Crossref) [2023-10-31] tex.orcid-numbers: Buford, Thomas W/0000-0002-9541-4358 Handberg, Eileen/0000-0002-7805-9577 Newman, Mark/0000-0002-0444-8246 tex.researcherid-numbers: Buford, Thomas W/B-1111-2011 Katula, Jeffrey/K-5905-2013 tex.unique-id: ISI:000324170300001
Keywords: Accelerometry; Aged; Aged; 80 and over; Aging; Compromised physical function; Exercise; Female; Health Promotion; Humans; Independent Living; Male; Mobility Limitation; Older adults; Physical disability; Qualitative Research; Risk Reduction Behavior; Sex Distribution; accelerometry; aged; aging; article; autoregulation; body mass; compromised physical function; computer interface; computer program; conceptual framework; controlled study; dept.hms; education; elderly care; ethnicity; exercise intensity; female; health education; human; human experiment; lifestyle; male; motor performance; normal human; older adults; phase 3 clinical trial; physical activity; physical capacity; physical disability; quality of life; randomized controlled trial; semi structured interview; sex difference; social behavior; social environment